A study on the effects of perceived playfulness and emotional support in interactive learning environments for German language acquisition—A role-playing library system case - Yang, Yunshuo; Lin, Jiacheng; Chen, Tong; Lin, Shuyuan; Chen, Jiangjie; Miao, Wei; Wei, Wei; Sun, Hanchu; Sun, Jie; Gu, Chao (Frontiers in Psychology, 2022)
Introduction This study examines the emotional support offered by the non-player characters (NPCs) in an interactive learning environment, as well as the effects of the perceived playfulness of the interactive system on German language learning. Method We developed a role-playing library system to serve this purpose. 2,377 Chinese Internet users were surveyed using online questionnaire. Results A theoretical model of emotion- driven learning (ELM) was proposed based on the analysis results of valid recovered data. Additionally, NPCs were found to be effective in improving learning outcomes through emotional support. Discussion An interactive education system may be able to enhance the perceived playfulness of learning in order to enhance the learning experience.